1987
DOI: 10.1039/dt9870003055
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electrochemical properties of bis(pyridine)cobalt(III) complexes of N,N′-ethylenebis(salicylideneimine) homologues with an aryl substituent on the ethylene backbone. Crystal structures of [Co(salpen)(py)2]PF6·0.5 Et2O and [Co(salcppn)(py)2]PF6·2py (py = pyridine)

Abstract: ChemInform Abstract The title complexes (Ia) are prepared by known methods. (Ib)-(Id) are obtained in the reaction of the Schiff base in MeOH with Co acetate in the presence of NaOH and Py under reflux, followed by addition of KPF6 in water. (Ib) crystallizes in the space group P1 with Z=2, (Ic) in P21/n with Z=4. The ethylene conformation is gauche for both complexes. The Co(III)/Co(II) reduction potentials of the complexes are not affected by mono-substitution on the ethylene carbon but change on disubstitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Due to the increased strain in a planar structure, however, we consider such a conform ation as unlikely. This assum ption is in accordance w ith structural results at com plexes o f ethylene-bridge substituted hom ologues o f salen [23]. The voltam m ogram s were analyzed quantita tively according to such an Eqr m echanism .…”
Section: I3c Nmr Data Were Supplemented By Hc-cosy Hc Long Range mentioning
confidence: 50%
See 1 more Smart Citation
“…Due to the increased strain in a planar structure, however, we consider such a conform ation as unlikely. This assum ption is in accordance w ith structural results at com plexes o f ethylene-bridge substituted hom ologues o f salen [23]. The voltam m ogram s were analyzed quantita tively according to such an Eqr m echanism .…”
Section: I3c Nmr Data Were Supplemented By Hc-cosy Hc Long Range mentioning
confidence: 50%
“…Structures o f bis-pyridine cobalt(III) Schiff-base com plexes [23], oxygen adducts to Co(salen) [42], substrate adducts [43], or dim ers [27,28] Table I, bond lengths and angles in Table II The ethylene diam ine bridge in the salen ligand form s together with the central Co atom a fivem em bered ring. One o f the C atoms (here, C8) is placed above, and the other one (C9) below the plane through N2, Co and N l. Thus, in the crys tal, the N -C H 2-C H 2-N bridge attains a non-planar conform ation, forcing the two arom atic units o f the ligand from coplanarity.…”
Section: Rysta L Structure An Alysismentioning
confidence: 99%
“…Previous studies on hexacoordinated iron(III) complexes with a N 4 O 2 donor set have revealed that the bond distances and angles of the iron atom are sensitive to its spin state. The HS-to-LS spin state change involves depopulation of the e g orbitals, which have an antibonding character. This change is concomitant with the shortening of the iron-to-ligand bond distances.…”
Section: Resultsmentioning
confidence: 99%
“…The structural diversity of transition metal complexes of these ligands and the structure-function relationships of the resulting complexes have been the focus of extensive research in recent years [1][2][3][4][5][6][7][8][9][10][11][12]. Their facile synthesis and easily tunable steric, electronic, and catalytic properties have led to the wide application of transition metal Schiff base complexes [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%